2022
DOI: 10.54985/peeref.2209p3789644
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Flexible Wings With Metamaterial Functionalities

Abstract:  Excellent agreement with simulations  No damage under long-term resonance exc. Design idea and analysis www.metamechanics.net  Metamaterial pattern to control flight aerodynamics and acoustics  Full-scale 3D modeling  Explore possibilities of additive manufacturing and near-resonance flight conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These are lightweight structures (of a mass lower than 2% of an insect's total weight) that have a high load-bearing capacity, can cope with attacking aerodynamic forces 10, and accelerate the surrounding air to enable flight 11 . Multiple studies have shown that these abilities originate exclusively from the structure and distribution of a building material 10,12,13,14,15,16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are lightweight structures (of a mass lower than 2% of an insect's total weight) that have a high load-bearing capacity, can cope with attacking aerodynamic forces 10, and accelerate the surrounding air to enable flight 11 . Multiple studies have shown that these abilities originate exclusively from the structure and distribution of a building material 10,12,13,14,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…The advances in finite-element techniques enabled to reproduction of complex aerodynamic conditions of different types of flight and to investigate the influence of the material architecture on mechanical and aerodynamic characteristics of insect wings 17,18,19,20 . For example, it was found that intricate venation patterns of the dragonfly and hoverfly wings help to minimize the mass of the wing and to ensure the balance between flexibility and rigidity 21 .…”
Section: Introductionmentioning
confidence: 99%